(untitled) (Italian Journal of Public Health, 2006)
Background: The evidence-based medicine movement has extended its influence to other fields. In the area of quality improvement, the evidence-based approach stimulated the diffusion of practice guidelines as a relevant policy tool. Concurrently guidelines have become the object of a large body of research, including systematic reviews. Objective: To explore to what extent systematic reviews on guideline implementation strategies support health policy decisions in this area. Methods: The use of systematic reviews in terms of influencing decisions concerning quality of care will be examined by focusing, in particular on two dimensions – guidelines as policy tools and guidelines as an object of research - and finally to what extent these two dimensions match. Results/Discussion: We highlight three aspects of mismatching between research and policy: the characteristics of guidelines, the relationship between guideline development and implementation and the type of research question addressed. These aspects represent conceptual obstacles that further challenge the adoption of an evidence based approach and limit the use of systematic reviews in supporting policy decisions in the area of quality improvement